Testosterone-immunopositive primordial germ cells in the testis of the bullfrog, Rana catesbeiana - Sasso-Cerri, E. (2005)
In amphibia, steroidogenesis remains quiescent in distinct seasonal periods, but the mechanism by which spermatogenesis is maintained under low steroidogenic conditions is not clear. In the present study, testosterone location in the testes of Rana catesbeiana was investigated immunohistochemically during breeding (summer) and nonbreeding (winter) periods. In winter, the scarce interstitial tissue exhibited occasional testosterone immunopositivity in the interstitial cells but the cytoplasm of primordial germ cells (PG cells) was clearly immunopositive. By contrast, in summer, PG cells contained little or no immunoreactivity whereas strong immunolabelling was present in the well-developed interstitial tissue. These results suggest that PG cells could retain testosterone during winter. This androgen reservoir could be involved in the control of early spermatogenesis in winter and/or to guarantee spermiogenesis and spermiation in the next spring/summer. The weak or negative immunoreaction in the summer PG cells might reflect consumption of androgen reservoir by the intense spermatogenic activity from spring to summer. Thus, besides acting as stem cells, PG cells of R. catesbeiana could exert an androgen regulatory role during seasonal spermatogenesis.